2013
DOI: 10.1108/info-05-2013-0026
|View full text |Cite
|
Sign up to set email alerts
|

Internet going mobile: internet access and use in 11 African countries

Abstract: With computer and Internet penetration in most countries still very low, the mobile phone is increasingly becoming key entry point for Internet adoption on the continent. This is one of the main findings of the 2011/2012 ICT access and usage household and individual survey which reports that the emergence of Internet enabled mobile phones and lower bandwidth adaptations of applications, particularly social media, is driving the rapid diffusion of mobile internet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 10 publications
1
53
0
Order By: Relevance
“…In most countries, high ICT prices, lack of ICT skills, and lack of relevant e-services with the systems of trust, privacy, and security are identified as the main barrier for those who do have access to the internet (Stork, Calandro, & Gillwald, 2013). This research confirmed that intergenerational educational strategies and literacy and e-literacy campaigns are needed to enable access to e-services.…”
Section: Literature Reviewsupporting
confidence: 62%
“…In most countries, high ICT prices, lack of ICT skills, and lack of relevant e-services with the systems of trust, privacy, and security are identified as the main barrier for those who do have access to the internet (Stork, Calandro, & Gillwald, 2013). This research confirmed that intergenerational educational strategies and literacy and e-literacy campaigns are needed to enable access to e-services.…”
Section: Literature Reviewsupporting
confidence: 62%
“…In Nigeria, a few exceptions of studies with similar focus exist (Ajuwon, 2003;Nwagwu, 2007;Stork et al, 2013). Nonetheless, these studies did not focus on the patterns, quality, perceived trustworthiness, and utilization of online health information in making health-related decisions.…”
Section: Youth and The Use Of The Internet For Health Informationmentioning
confidence: 85%
“…Nevertheless one sees regional disparity of ICT access. In review of this global data, some "low" human development countries are experiencing high uptake in mobile phone subscriptions but low uptake of Internet usage (ITU 2011;Stork et al 2013): Technology is the tool, NOT the outcome. Judith Rodin (Rockefeller Foundation at the Social Good Summit, New York, September 2013) While the ITU statistics may distinguish between HDI and IDI levels, they do not distinguish between rich and poor households or individuals within countries.…”
Section: Measuring Icts In Developing Countriesmentioning
confidence: 99%